Dental visits in Medicaid-enrolled youth with mental illness: an analysis of administrative claims data - Erica L. Stockbridge; Eleena Dhakal; Stacey B. Griner; Abiah D. Loethen; Joseph F. West; Joseph W. Vera; Karabi Nandy (BMC, 2020)
Abstract Background State Medicaid plans across the United States provide dental insurance coverage to millions of young persons with mental illness (MI), including those with attention deficit hyperactivity disorder (ADHD), depression, anxiety, bipolar disorder, and schizophrenia. There are significant oral health challenges associated with MI, and providing dental care to persons with MI while they are young provides a foundation for future oral health. However, little is known about the factors associated with the receipt of dental care in young Medicaid enrollees with MI. We aimed to identify mental and physical health and sociodemographic characteristics associated with dental visits among this population. Methods We retrospectively analyzed administrative claims data from a Medicaid specialty health plan (September 2014 to December 2015). All enrollees in the plan had MI and were ≥ 7 years of age; data for enrollees aged 7 to 20 years were analyzed. We used two-level, mixed effects regression models to explore the relationships between enrollee characteristics and dental visits during 2015. Results Of 6564 Medicaid-enrolled youth with MI, 29.0% (95% CI, 27.9, 30.1%) had one or more visits with a dentist or dental hygienist. Within youth with MI, neither anxiety (Adjusted odds ratio [AOR] = 1.15, p = 0.111), post-traumatic stress disorder (AOR = 1.31, p = 0.075), depression (AOR = 1.02, p = 0.831), bipolar disorder (AOR = 0.97, p = 0.759), nor schizophrenia (AOR = 0.83, p = 0.199) was associated with dental visits in adjusted analyses, although having ADHD was significantly associated with higher odds of dental visits relative to not having this condition (AOR = 1.34, p < 0.001). Age, sex, race/ethnicity, language, and education were also significantly associated with visits (p < 0.05 for all). Conclusions Dental utilization as measured by annual dental visits was lower in Medicaid-enrolled youth with MI relative to the general population of Medicaid-enrolled youth. However, utilization varied within the population of Medicaid-enrolled youth with MI, and we identified a number of characteristics significantly associated with the receipt of dental services. By identifying these variations in dental service use this study facilitates the development of targeted strategies to increase the use of dental care in - and consequently improve the current and long-term wellbeing of - the vulnerable population of Medicaid-enrolled youth with MI.